2010
DOI: 10.1016/j.jvs.2009.11.067
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Treatment Assessment Project 2: A Multinational Survey to Evaluate the Proportion of Patients Achieving Low-Density Lipoprotein Cholesterol Goals

Abstract: excised down to the level of the deep muscle fascia from the knee to the dorsum of the foot. The wound was covered with 12-to 16/1000-inch split thickness skin grafts harvested from the ipsilateral leg. For those who underwent elective toe amputations, toe disarticulation at the metatarsalphalangeal joint was combined with removal of the articular cartilage from the metatarsal heads. Average follow-up was 3.5 years. During follow-up, 20% of the patients who underwent combined Charles procedure and elective toe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
103
2
7

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(122 citation statements)
references
References 0 publications
10
103
2
7
Order By: Relevance
“…The methods used in L-TAP 2 have been described previously [8]. In brief, patients were eligible if they were aged !20 years, and if they had been treated with the same lipid-lowering therapy for !3 months.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The methods used in L-TAP 2 have been described previously [8]. In brief, patients were eligible if they were aged !20 years, and if they had been treated with the same lipid-lowering therapy for !3 months.…”
Section: Methodsmentioning
confidence: 99%
“…The Lipid Treatment Assessment Project 2 (L-TAP 2) was a multicenter survey of lipid goal attainment in dyslipidemic patients who were on stable lipid-lowering therapy at investigation sites in 9 countries (Canada, Brazil, Mexico, the USA, France, Spain, the Netherlands, South Korea, and Taiwan) between September 2006 and April 2007 [8]. This current pre-specified analysis of the L-TAP 2 survey describes the attainment of non-HDL-C goals according to the level of risk and compared with LDL-C goal attainment in the whole study population, as well as according to gender, baseline plasma TG levels ( 200 mg/dL vs. >200 mg/dL), and world region.…”
Section: Introductionmentioning
confidence: 99%
“…Statins are the mainstay of lipid-lowering drug (LLD) therapy and have been shown to reduce both LDL-C levels and CV risk in clinical trials [9][10][11][12][13][14][15][16] . Despite the significant increase in the number of patients treated with statins and other LLDs over the past decade, surveys have shown that relatively few individuals eligible for treatment attain their recommended LDL-C level [17][18][19] . …”
mentioning
confidence: 99%
“…575 LDL-C after 12 months 17) . However, the Lipid Treatment Assessment Project 2 (L-TAP2) study 19) , reported a higher rate of LDL-C goal attainment than the combined CEPHEUS studies. The L-TAP2 study was conducted in nine countries across Europe (France, Netherlands, and Spain), the Americas (USA, Canada, Brazil, and Mexico) and Asia (South Korea and Taiwan), and 73% of 9955 evaluated patients were shown to have attained their LDL-C goal.…”
mentioning
confidence: 99%
“…A considerable amount of research exploring treatment gaps has been conducted in patients with CAD. [17][18][19][20][21] Research in patients with NCIS or TIA appears to demonstrate similar findings and highlights important treatment gaps among this population. Although there are considerably fewer studies by which to draw conclusions compared with the CAD literature, studies report that …”
Section: Discussionmentioning
confidence: 67%